The overspent American why we want what we don't need - Schor, Juliet; Garner, Kelly (United States : Media Education Foundation, 2007)
Film explains the cultural forces behind Americans overspending in order to demonstrate material success. The overspent American challenges the inevitability of the consumer lifestyle by proposing alternatives to the work and spend cycle that has so many Americans feeling trapped and fulfilled
The cycle of work and spend -- Stretching reference groups -- The visible lifestyle -- The costs of overspending -- Getting off the consumer escalator -- Downshifting -- Kid spending -- Lipstick -- SUV advertising
Title from title screen
Executive producers, Sut Jhally ; editor, camera, Kelly Garner
Juliet Schor
In English with optional English and Spanish subtitles
Keywords: Consumer behavior -- United States; Consumption (Economics) -- United States; Credit -- United States; Debt -- United States; Finance, Personal -- United States; Lifestyles -- United States